Postmodern Fanaticism in Historiographic Metafiction: A Study of Tanushree Podder’s Escape from Harem - Dheebha, A. M. Kumari; A. Nisha (International Journal of Psychosocial Rehabilitation, 2020)
The postmodern historiography not only represents past events but also adds colours to the events and makes it as a signifying system. In this narrative, history is being rethought as a human construct. It becomes a fictional act to elaborate events through the magic of language and takes the readers to a realistic world. Historiographic metafiction is a post modern critical innovation in literature and it is characterized by intense ‘self-reflexivity’ and ‘parodic intertextuality’. The present article attempts to validate Tanushree Podder’s Escape from Hare with the aspects of Linda Hutcheon’s theory of historiographic metafiction. It tries to portray that the novel is a historiographic metafiction rather than the traditional historical fiction. It examines the relationship between the reimagined and reconstructed historiographic metafiction. The study discusses the narrative style of the author which is in the mimetic approach. It reassesses the unknown facts of the marginalized women of the sixteenth century Mughal dynasty. It leads to the fact that marginalized groups are denied an official voice by hegemonic ideologies. Therefore, history is regarded as monologic, represented the dominant discourse.